EFFECTIVENESS OF FRACTIONAL CARBONDIOXIDE LASER WITH TOPICAL METHOTREXATE VS TOPICAL PUVASOL IN TREATEMENT OF VITILIGO - Samina; Sakina Sadiq Malik; Ahmed Naveed Malik; Aayesha Rehman; Sajjad Ahmed; Ahsan Tameez-Ud-Din (Journal of Ayub Medical College Abbottabad, 2026)
Background: Vitiligo is an autoimmune disease characterized by patches of depigmentation on the skin. As skin is the major contributor to one’s social image and appearance, this disease impairs one’s quality of life to a significant extent. Dermatologists are continuously trying to find more and better treatment options, in addition to steroids, calcineurin inhibitors, immunomodulators and phototherapy. The aim of our study was to compare the effectiveness of topical methotrexate in combination with fractional carbon dioxide laser with topical psoralen with solar UVA (PUVASOL). Our hypothesis was that the Carbon dioxide laser-Topical Methotrexate combination is better than topical PUVASOL. It was a double blinded randomized Control Trial carried out in the Dermatology OPD of a tertiary care hospital in Rawalpindi over a period of 06 months i.e., 20.01.24 to 20.07.24. Methods 36 patients meeting the inclusion criteria were included in the study after taking informed consent. Sampling was done by non-probability randomized sampling using lottery method. Half of them were treated with Fractional CO-2 laser followed by topical methotrexate12.5mg/ml application. Weekly sessions were done for 4 months. In the other group topical PUVASOL was used on alternate days for 04 months. 01 patient from each group was dropped. An independent observer noted the clinical improvement. Patient satisfaction and complications were also recorded. Results Statistically significant difference in results of Group A as compared to Group B, regarding clinical improvement and patient satisfaction were noted i.e., p= 0.039 and 0.002 respectively. There was no significant difference in the side-effect profile of both groups (p=0.59), with 44.1% patients having no side effect at all. Conclusion: Fractional Carbon dioxide laser combined with topical methotrexate is better than topical PUVASOL in the treatment of vitiligo. Keywords Fractional carbon dioxide laser, Topical methotrexate, Topical PUVASOL, Vitiligo